Mechanotransduction of cells under physical constraints - Koh, Xiao Woon. (2010)
Cell motility is a dynamic phenomenon that is essential to biological processes. It is brought about by cell traction forces (CTFs) which are internal tensile forces generated by cells through actomyosin interactions and transmitted to extracellular matrix (ECM) via focal adhesions. In this study, mechanotransduction of cells under physical constraints was studied through the incorporation of microcontact printing technique and cell traction force microscopy (CTFM). Type I collagen molecules of different geometries were stamped using microcontact printing technique onto polyacrylamide (PAL) gel embedded with fluorescent microbeads. Smooth muscle cells (SMC) were cultured on the collagen patterns. CTFs exerted by cells were measured through microbeads’ displacement field which was quantified using the Particle Image Velocimetry (PIV) method, based on Minimum Quadratic Differences (MQD) algorithm. Displacement vector field was input into Finite Element Analysis (FEA) as the boundary condition to simulate the traction stresses according to the global mechanical properties of the PAL gel. For rectangular-shaped collagen islands, CTFs were exerted mainly from the elongated tips of cells with high aspect ratios and from the corners of cells with low aspect ratios to the centre of cells. The absence of vectors in the center regions of the displacement vector plots was because CTFs were normal to the PAL gel and not reflected in the two-dimensional plots. Cells which occupied a larger area or higher aspect ratio exerted larger CTFs on the PAL gel. The likelihood of cell length affecting the CTFs was also higher than that of cell width.